1985
DOI: 10.1111/j.1600-0714.1985.tb00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical studies of obstructive adenitis in human submandibular salivary glands. II. Lectin binding and keratin distribution in the lesions

Abstract: Lectin‐binding profiles and keratin distribution in obstructive adenitis of human submandibular glands (SMGs) are reported and compared those of normal SMGs. Histologically, obstructive changes in the SMGs included acinar atrophy, duct‐like structure formation in the early stage, and disappearance of acinar cells and dilation of ductal segments in the later, chronic stage. The following lectins were used: Con A (Glc. Man), PNA(Gal, GalNAc). RCA1I(Gal), DBA(GalNAc). SBA(Gal, Gal‐NAc). UEA‐1(α‐L‐Fuc) and WGA((Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…These cells were sometimes in the process of forming vessel walls but at other times were not yet assembled into blood vessels. Although the duct epithelial nature of their constituent cells has been well investigated by ultrastructural [2,5,9,11,19,28,32,35,40,41] and immunohistochemical [3,15,16,21,22,26,27,32,38] studies, there has been no postulation of endothelial cell participation in the formation of LELs. Only Qin et al [29] reported von Willebrand factor-immunopositive capillaries in the inflammatory stroma, suggesting that an efficient blood supply elucidates regeneration and proliferation of epithelial cells in the formation of the LELs in a general sense.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells were sometimes in the process of forming vessel walls but at other times were not yet assembled into blood vessels. Although the duct epithelial nature of their constituent cells has been well investigated by ultrastructural [2,5,9,11,19,28,32,35,40,41] and immunohistochemical [3,15,16,21,22,26,27,32,38] studies, there has been no postulation of endothelial cell participation in the formation of LELs. Only Qin et al [29] reported von Willebrand factor-immunopositive capillaries in the inflammatory stroma, suggesting that an efficient blood supply elucidates regeneration and proliferation of epithelial cells in the formation of the LELs in a general sense.…”
Section: Discussionmentioning
confidence: 99%
“…EMIs were first investigated using electron microscopy (EM) in the 1960s [2,5,9,11,19,28,32,35,40,41] and were shown to be composed of both duct epithelial and myoepithelial cells. However, immunohistochemical studies for cytoskeletal proteins were introduced in this lesion in the 1980s, which indicated that cells with duct epithelial characteristics are mainly responsible for the EMI formation [3,15,16,21,22,26,27,32,38]. In addition to the EM studies, these immunohistochemical studies have also indicated that the EMIs are composed of not only epithelial cells but also of other inflammatory cells, as not all of the constituent cells of EMIs are immunolabeled for epithelial cytoskeletal proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This histopathology of obstructed salivary gland lesions has been well established, and the keratin staining pattern of the lesions has also been reported with the use of polyclonal antibody (24,28). Existence of K8.12 staining in ductal basal cells of obstructive lesions was first noted in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…Early obstructive lesions mainly showed ductal dilation and a little atrophy of acinar compartments accompanied by infiltrating inflammatory cells. When long-standing obstruction occured in the glands, almost all acinar cells disappeared or degenerated with fibrous tissue replacement and ductal segments remained in a fibrous stroma (24).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, ductal epithelia and acinar cells, either serous or mucous, of normal glands indicated negative staining as did duct-like structures in obstructive sialadenitis. Keratin staining is strongly evident in epithelial architecture, i.e., normal ductal segments of salivary glands and duct-like structures of sialadenitis (2,3,6,12). This finding suggests that the duct-like structures in obstructive salivary lesions have less tendency to terminal keratinization.…”
Section: Discussionmentioning
confidence: 89%